Redazione e validazione della versione di screening del Bilingual Aphasia Test (BAT) in cinese mandarino - Corsi, Giulia; Sushanghua, Xia; Panunzi, Alessandro (CHIMERA: Revista de Corpus de Lenguas Romances y Estudios Lingüísticos, 2022)
This work describes the implementation of the Bilingual Aphasia Test (BAT) screening version for Mandarin Chinese. This short version is derived from the Full BAT, according to the authors specification, and allows to assess linguistic abilities of the two (or more) languages spoken by a bilingual patient. This tool has been initially developed in a traditional paper and pencil form, and then adapted in a digital format to be remotely administered through the web. Preliminary results of tuning and validation of this screening are available and confirm the foreseen high percentage of accuracy obtained on a normative sample.